Data Scientist Careers: Applied Orientation for the Beginners - Pasupuleti, Mahesh Babu (Global Disclosure of Economics and Business, 2016)
A data scientist's job is making sense of complex, unstructured data that comes from a variety of sources, including smart devices, social media feeds, and emails, and that doesn't cleanly fit into a database structure. According to the findings of this study, Data Scientists require programming, mathematics, and database abilities, all of which may be learned by self-study or through formal education. Companies looking to hire a Data Science team must be aware of the wide range of tasks that Data Scientists may fill, as well as the need for soft skills such as storytelling and connection building in addition to technical abilities and knowledge. The interpretation emphasizes that high school students interested in pursuing a career in Data Science should learn programming, mathematics, databases, and, most importantly, exercise their newfound knowledge. The study's findings centered on data scientists as analytical specialists who employ their expertise in both technology and social science to discover patterns and manage data. The solutions to business difficulties are discovered via the use of industry expertise, contextual awareness, and skepticism of current assumptions.